Calculation of Pollutant Load in Cipunagara River: Livestock Sector - Iwan Juwana; Diki Prastyo Nugroho (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Cipunagara is the largest watershed in Subang Regency with River Cipunagara as the mainstream. Previous works showed increased activities around Cipunagara watershed, especially in segment 3, leading to a decline in the water quality. The importance of this river increases due to the development plan of Sadawarna and Cilame Reservoirs, which are used for irrigation and other activities. This study aims to identify pollution sources and to analyze the capacity of Cipunagara River in relation to potential pollution load from the watershed for the next 5 years. The study focuses on livestock, which is one of the main sectors contributing to pollution. The main steps include segment selection, calculation of existing pollutant load and prediction within the next 5 years from livestock waste. The segment selection was based on the number of activities from several sectors, the spatial plan of the region, as well as the quality and quantity Cipunagara River. The calculation of existing pollutant load was based on actual pollutant and flow of the river, while the prediction of pollutant load relied on emission factor of each pollutant parameter. The results showed that pollution index in Cipunagara River was severe. The existing and the projected potential pollutant loads in segment 3 include 1,668.76 kg/day and 2,081.25 kg/day for BOD; 4,053.74 kg/day and 5,063.29 kg/day for COD; 8.72 kg/day and 13.34 kg/day for N-Total; and 1.75 kg/day and 2.16 kg/day for P-Total, respectively. These results can be used by the local governments to manage water quality of the river.